2020
DOI: 10.1101/2020.03.08.982249
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precision engineering of the transcription factor Cre1 inHypocrea jecorina (Trichoderma reesei)for efficient cellulase production in the presence of glucose

Abstract: In Trichoderma reesei, carbon catabolite repression (CCR) significantly downregulates the transcription of cellulolytic enzymes, which is usually mediated by the zinc finger protein Cre1. It was found that there is a conserved region at the C-terminus of Cre1/CreA in several cellulase-producing fungi that contains up to three continuous S/T phosphorylation sites. Here, S387, S388, T389, and T390 at the C-terminus of Cre1 in T.reesei were mutated to valine for mimicking an unphosphorylated state, thereby genera… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 24 publications
0
3
0
1
Order By: Relevance
“…The authors gratefully acknowledge Prof. Luying Xun's help in revising this manuscript. The part contents in this article have been released as a pre-print at BioRxiv (Han et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…The authors gratefully acknowledge Prof. Luying Xun's help in revising this manuscript. The part contents in this article have been released as a pre-print at BioRxiv (Han et al, 2020).…”
Section: Data Availability Statementmentioning
confidence: 99%
“…Interestingly, the phosphorylation of Cre1 at S241 is required for DNA binding [8] . Recently, Han et al, in order to evaluate the influence of phosphorylation on the transcription factor Cre1 in T. reesei and its effect on the expression of cellulolytic enzymes, mutated several residues at C terminus of Cre1 to mimic dephosphorylation and observed that there was an improvement in cellulase transcription levels and activity in the presence of glucose and inhibition of carbon catabolite repression [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Post‐translational modifications, particularly phosphorylation and dephosphorylation, may play a critical role in signal perception, transmission, and subsequent cellular responses during adaptation of filamentous fungi to plant cell wall polysaccharides (Horta et al, 2019; Rodriguez‐Iglesias & Schmoll, 2019; Schmoll, 2018; Xiong, Coradetti, et al, 2014). Phosphorylation of CRE‐1 has been found to be required for binding to its target sequences in Trichoderma reesei and for triggering CCR (Cziferszky et al, 2002; Han et al, 2020). Six non‐essential protein phosphatases were found to be positive or negative regulators for lignocellulase production in T .…”
Section: Introductionmentioning
confidence: 99%